2021
DOI: 10.3390/nano11123382
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogel-Derived Synthesis of Porous PdFe Nanohydrangeas as Electrocatalysts for Oxygen Reduction Reaction

Abstract: It is important to develop cost-efficient electrocatalysts used in the oxygen reduction reaction (ORR) for widespread applications in fuel cells. Palladium (Pd) is a promising catalyst, due to its more abundant reserves and lower price than platinum (Pt), and doping an earth-abundant 3d-transition metal M into Pd to form Pd–M bimetallic alloys may not only further reduce the use of expensive Pd but also promote the electrocatalytic performance of ORR, owing to the synergistic effect between Pd and M. Here we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Cyanogel, formed by the repeated coordination of metal ion and cyanogroup (M-CN-M', M ¼ Fe, Co, Ni, Pd, Pt), can be used as ideal precursors for noble metal-based alloy catalysts with 3D structures. [45,46] Cyanogel reduction has several unique merits: i) The preparation process is simple and the gelling conditions are not limited by air humidity, temperature and pressure for catalysts. [47,48] ii) Uniform distribution of metal ions at the atomic scale in cyanogel facilitates the formation of alloy phases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyanogel, formed by the repeated coordination of metal ion and cyanogroup (M-CN-M', M ¼ Fe, Co, Ni, Pd, Pt), can be used as ideal precursors for noble metal-based alloy catalysts with 3D structures. [45,46] Cyanogel reduction has several unique merits: i) The preparation process is simple and the gelling conditions are not limited by air humidity, temperature and pressure for catalysts. [47,48] ii) Uniform distribution of metal ions at the atomic scale in cyanogel facilitates the formation of alloy phases.…”
Section: Introductionmentioning
confidence: 99%
“…[50] Moreover, NaBH 4 , as a strong reducing agent, can rapidly reduce Pd and Cu ions to achieve the formation of PdCu alloy. [45] At present, the reported Pd-based cyanogels include Pd [45][46][47]51] The lack of research on PdCu cyanogel may be largely attributed to the instability of K 2 [Cu(CN) 4 ], which easily decomposes to copper (I) cyanide and releases toxic cyanide gas at room temperature (2CuðCNÞ 2À 4 ! ðCNÞ 2 þ 2CuðCNÞ 2À 3 ), thus limiting the formation of PdCu alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its small impact on the environment, high power density, and high energy conversion efficiency, it is increasingly favored by researchers. ( Gao et al, 2020 ; He et al, 2020 ; Prithi et al, 2021 ; Wan et al, 2021 ; Kurdin et al, 2022 ; Liu et al, 2022 ) However, it is limited by the expensive cost of Pt-based catalysts at the anode and cathode for widespread development. Research found that the ordered intermetallic compounds served as effective electrocatalysts solve the current dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic nanocatalysts are a type of heterogeneous catalyst that contains two metal components within a single catalyst and whose composition, size, and configuration can be reasonably controlled. More importantly, it exhibits higher catalytic activity and better selectivity and stability than those of monometallic analogs due to the synergistic effects between the two metallic elements [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In recent decades, several laboratories have focused on the exploitation of non-noble metals and Pd nanoalloy catalysts, such as Pd-Co [ 11 ], Pd-Ni [ 12 ], Pd-Cu [ 13 ], Pd-Mn [ 14 ], and Pd-Fe [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%